2018
DOI: 10.3390/nu10111745
|View full text |Cite
|
Sign up to set email alerts
|

A Calcium-Deficient Diet in Dams during Gestation Increases Insulin Resistance in Male Offspring

Abstract: Calcium (Ca) plays an important role in the pathogenesis of insulin resistance syndrome. Osteocalcin (OC), a bone formation biomarker, acts directly on β-cells and increases insulin secretion. We determined the effects of Ca deficiency during pregnancy and/or lactation on insulin resistance in offspring. Female Wistar rats consumed either a Ca-deficient or control diet ad libitum from three weeks preconception to 21 days postparturition. Pups were allowed to nurse their original mothers until weaning. The offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The offspring were then sacrificed at an age of 180 days. The mean levels of insulin and glucose as well as the HOMA-IR values were higher only in the male offspring from the Ca-deficient dams than in those from the control dams (p < 0.01) [82]. In all offspring, the serum leptin levels were correlated with the serum insulin levels, and they were inversely correlated with the levels of ionized Ca.…”
Section: A Ca-deficient Diet In Dams During Gestation Increases Insulin Resistance In Male Offspringmentioning
confidence: 81%
See 1 more Smart Citation
“…The offspring were then sacrificed at an age of 180 days. The mean levels of insulin and glucose as well as the HOMA-IR values were higher only in the male offspring from the Ca-deficient dams than in those from the control dams (p < 0.01) [82]. In all offspring, the serum leptin levels were correlated with the serum insulin levels, and they were inversely correlated with the levels of ionized Ca.…”
Section: A Ca-deficient Diet In Dams During Gestation Increases Insulin Resistance In Male Offspringmentioning
confidence: 81%
“…Glu-OC acts directly on pancreatic β-cells to increase insulin secretion, as well as insulin sensitivity and glucose tolerance [86][87][88]. The offspring rats of the same experimental methods as described in the previous section were raised to adults [82]. The mean levels of Glu-OC in Ca-deficient female offspring were higher than those in control female offspring and control male offspring.…”
Section: Osteocalcin In the Offspring From A Ca-deficient Damsmentioning
confidence: 99%
“…Takaya et al found that in rat models, a maternal Ca-deficient diet increased insulin resistance in the adulthood of offspring, especially in male offspring. This alteration may be involved in the influenced hepatic hydroxysteroid 11-beta dehydrogenase 1 (Hsd11b1) expression (49) and the altered osteocalcin, a bone formation biomarker, that acts directly on pancreatic β-cells and increases insulin secretion (50). The undercarboxylated osteocalcin (Glu-osteocalcin) was increased to 76.7 ± 48.4 ng/mL in female offspring fed on a maternal low Ca diet, compared with 19.6 ± 9.9 ng/mL in control group (50).…”
Section: Minerals Calciummentioning
confidence: 99%
“…Evidence in rats showed both maternal low- and high-salt diets lead to elevated BP in male adult offspring [69]. Additionally, maternal calcium-deficient diet increased BP and insulin resistance in adult rat offspring [70,71]. Furthermore, magnesium-deficient diet in pregnancy caused impaired kidney function but had no effect on BP in rat offspring [72].…”
Section: Insights From Animal Models Of Nutritional Programmingmentioning
confidence: 99%